Benefits of spirituality and/or religiosity in patients with Chronic Kidney Disease: an integrative review - Bravin, Ariane Moyses [UNESP]; Trettene, Armando dos Santos; Modelli de Andrade, Luis Gustavo [UNESP]; Popim, Regina Celia [UNESP] (Assoc Brasileira Enfermagem, 2019)
Objective: Identify and analyze existing evidence regarding the benefits of spirituality and / or religiosity in patients with Chronic Kidney Disease. Method: Integrative review carried out through consultation of databases: Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, US National Library of Medicine and Scopus. The following descriptors were used: chronic kidney disease, spirituality and religion. Primary articles published by December 2017 were included. Results: Twenty-six articles were selected, from which four thematic categories emerged: benefits as a modality of coping, perception of quality of life, mental health and improvement of renal function after transplantation. Conclusion: Benefits included those related to situational coping modalities, such as the strengthening of hope, social support and coping with pain; those related to mental health, such as the lower risk of suicide and fewer depressive symptoms; improvement in the perception of quality of life and in renal function after transplantation.
Keywords: Chronic Kidney Disease; Spirituality; Religion; Religion and Medicine; Patient-Centered Care